PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) PADA PERBANKAN SYARIAH DI INDONESIA - Efendi, Alfarisi Akbar (UNPERBA, 2024)
This research aims to analyze and provide empirical evidence regarding the influence of corporate governance and company characteristics on Islamic Social Report (ISR) disclosure in Islamic banks in Indonesia. This analysis uses independent variables: commissioner size, sharia supervisory board, company size, leverage and profitability. Meanwhile, the dependent variable is Islamic Social Reporting. The sample used in this research is sharia banking in Indonesia which reports its annual reports for the 2013-2016 period.